Effect of self-efficacy sources and attitude on pronunciation learning strategies among EFL learners in China - Zou, Shuli; Karpal Singh, Paramjit Kaur (International Journal of Evaluation and Research in Education (IJERE), 2025)
Pronunciation learning is a crucial yet often neglected aspect of second language acquisition, particularly for English as a foreign language (EFL) learner. However, the factors influencing effective pronunciation learning strategies (PLS) remain underexplored. This study aims to address this gap by investigating the effects of self-efficacy sources (mastery experiences, vicarious experiences, social persuasion, and physiological/emotional states) and attitude (cognitive, conative, and affective components) on the adoption of PLS among EFL learners in China. To explore these relationships, a quantitative approach was employed, using structural equation modeling to analyze data from 320 EFL students. The results reveal that self-efficacy sources, namely, mastery experiences and vicarious experiences, have a positive and significant effect on PLS, while verbal persuasion and psychological state have an insignificant impact on PLS. Moreover, findings indicate that cognitive and conative attitudes were found to have a positive and significant impact on PLS, whereas affective attitudes had no significant effect on PLS. This study contributes to the growing body of research on pronunciation learning by providing insights into how psychological factors can shape EFL learners’ strategy use, offering implications for language educators to support students in improving their pronunciation skills.